Psychological Hardiness as a Protective Factor in Women Undergoing Reproductive Treatments - Mahmoudimozafar , Majid (Psychology of Woman Journal, 2023)
Objective: This study aims to explore the role of psychological hardiness as a protective factor in women undergoing reproductive treatments.Methods and Materials: A qualitative research design was employed, utilizing semi-structured interviews with 26 women undergoing reproductive treatments in Tehran. Participants were selected through purposive sampling, and data collection continued until theoretical saturation was reached. Thematic analysis was conducted using NVivo software to identify key themes and patterns in the participants’ experiences. Trustworthiness of data was ensured through peer debriefing, member checking, and an audit trail.Findings: Four main themes emerged: emotional resilience, cognitive strategies, social interactions, and coping resources. Participants highlighted the importance of stress regulation, self-soothing, and emotional detachment in fostering resilience. Cognitive strategies, such as reframing challenges, goal setting, and problem-solving, were instrumental in managing infertility-related stress. Social support networks provided emotional sustenance, though societal stigma remained a challenge. Coping resources, including physical health maintenance, spiritual practices, and professional assistance, further enabled participants to navigate the emotional and psychological burdens of infertility.Conclusion: Psychological hardiness plays a critical role in mitigating the emotional and cognitive challenges of infertility, offering women a pathway to resilience and well-being. Integrating psychological interventions, social support systems, and culturally sensitive care into infertility treatment programs can significantly enhance outcomes for women undergoing reproductive treatments. Further research is needed to explore the long-term impact of hardiness-focused interventions in diverse cultural contexts.